Long term effectiveness of electrochemotherapy for the treatment of lower lip squamous cell carcinoma. Issue 11 (November 2018) - Gargiulo, M.; Serra Mestre, J.M.; Cortese, A.; Murphy, D.C.; Parascandolo, S.; Razzano, S.
Abstract: Purpose: Electrochemotherapy (ECT) is a therapeutic approach based on the local application of electrical pulses that permeabilize cell membranes to enhance the uptake of low-permeant chemotherapeutic agents, thus increasing their cytotoxic effects. Materials and methods: Twenty-one patients with SCC of the lower lip were treated according to the European Standard Operating Procedures of Electrochemotherapy. Bleomycin (15, 000 IU/m 2 body surface area) was administered intravenously over a 1-min period. Eight electrical pulses (amplitude, 1000 V/cm; duration, 100 μs) were generated and delivered at a repetition frequency of 5 kHz. Changes in tumor volume were used to assess treatment response. Results: Objective response (OR), complete response (CR), and partial response (PR) rates of 100%, 71.4%, and 28.6% respectively were demonstrated following a single session of ECT. ECT was well tolerated, and no adverse events occurred. Conclusions: Intravenous bleomycin-based ECT is a safe and effective therapy for SCC of the lower lip. ECT improves the quality-of-life of patients by preserving the function and the aesthetic appearance of the affected area. ECT provides a therapeutic option for elderly and frail patients who, due to their state of health, are not suitable for, or refuse surgical interventions.